2022
DOI: 10.1051/0004-6361/202243683
|View full text |Cite
|
Sign up to set email alerts
|

Phase-resolved spectroscopic analysis of the eclipsing black hole X-ray binary M33 X-7: System properties, accretion, and evolution

Abstract: M33 X-7 is the only known eclipsing black hole high mass X-ray binary. The system is reported to contain a very massive O supergiant donor and a massive black hole in a short orbit. The high X-ray luminosity and its location in the metal-poor galaxy M33 make it a unique laboratory for studying the winds of metal-poor donor stars with black hole companions and it helps us to understand the potential progenitors of black hole mergers. Using phase-resolved simultaneous HST-and XMM-Newton-observations, we traced t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…However, such low birth masses are in conflict with BHs in high-mass X-ray binaries (HMXBs), where a compact object accretes matter from the stellar winds of a young and massive (5 M e ) companion. Of the many known HMXBs (>100 in the MW alone; see the recent catalogs of Fortin et al 2023;Neumann et al 2023), three are known to host dynamically confirmed BHs: Cygnus X-1, with a BH mass of 21.2 ± 2.2 M e and an age of ∼4 Myr (Miller-Jones et al 2021); LMC X-1, with a BH mass of 10.91 ± 1.41 M e and an age of ∼5 Myr (Orosz et al 2009); and M33 X-7, with a BH mass of 11.4 M e and an age of ∼5.8 Myr (Ramachandran et al 2022). Because their accretion is fed from the winds of the companion, these BHs likely have masses close to their natal values.…”
Section: Could Horizonless Bhs Form With Subsolar Masses?mentioning
confidence: 99%
“…However, such low birth masses are in conflict with BHs in high-mass X-ray binaries (HMXBs), where a compact object accretes matter from the stellar winds of a young and massive (5 M e ) companion. Of the many known HMXBs (>100 in the MW alone; see the recent catalogs of Fortin et al 2023;Neumann et al 2023), three are known to host dynamically confirmed BHs: Cygnus X-1, with a BH mass of 21.2 ± 2.2 M e and an age of ∼4 Myr (Miller-Jones et al 2021); LMC X-1, with a BH mass of 10.91 ± 1.41 M e and an age of ∼5 Myr (Orosz et al 2009); and M33 X-7, with a BH mass of 11.4 M e and an age of ∼5.8 Myr (Ramachandran et al 2022). Because their accretion is fed from the winds of the companion, these BHs likely have masses close to their natal values.…”
Section: Could Horizonless Bhs Form With Subsolar Masses?mentioning
confidence: 99%
“…Supergiant/giant companion stars have been observed in HMXB systems in other galaxies with both black hole and neutron star accretors. Black hole HMXBs (BH-HMXBs) such as Cyg X-1 (Orosz et al 2011), LMC X-1 (Orosz et al 2009), and M33 X-7 (Orosz et al 2007;Ramachandran et al 2022, which is included in our sample as Source ID 225) all comprise black holes accreting from supergiant companion stars with masses 30 M e , suggesting they are very young systems because 30 M e stars have maximum lifetimes 10 Myr. Neutron star HMXBs with supergiant companion stars are also thought to be very young systems.…”
Section: Hard X-ray Properties Of M33 Hmxb Candidatesmentioning
confidence: 99%
“…There are also two eclipsing X-ray binaries in M33 (Pietsch et al 2004(Pietsch et al , 2006(Pietsch et al , 2009. One of the two, M33 X-7, comprises a massive stellar-mass black hole in orbit with an O-type stellar companion (Orosz et al 2007;Ramachandran et al 2022). The exact orbital separation and masses of the black hole and companion star in M33 X-7 have been debated, but the system has provided interesting constraints for massive binary stellar evolution models.…”
Section: Introductionmentioning
confidence: 99%
“…Orosz et al (2009) estimate it to have a donor mass of (31.8 ± 3.5)M e and a BH accretor mass of (10.9 ± 1.4)M e . Another resolved extragalactic HMXB is M33 X-7, an HMXB in the spiral galaxy M33 estimated to have a BH (Ramachandran et al 2022). Similar to Galactic HMXBs, the population of well-constrained extragalactic sources is small, and in this case, none are found to harbor BH accretors >20 M e .…”
Section: Introductionmentioning
confidence: 99%